ANALISIS PENERIMAAN SISTEM INFORMASI DAN TEKNOLOGI DALAM PENINGKATAN PELAYANAN DIGITAL LIBRARY DI JURUSAN EKONOMI SYARIAH FAKULTAS EKONOMI DAN BISNIS ISLAM INSTITUT AGAMA ISLAM NEGERI TULUNGAGUNG - Nur Aziz Muslim; Bamabang Triyono (Among Makarti, STIE AMA Salatiga, 2019)
Abstract The research objective includes the content and formulation of research problems. The purpose of this study is a) to determine the effect of the reception of information systems and technology models in improving digital library services in the department of Islamic economics, Faculty of Economics and Business, Islamic Institute of Islamic Affairs, Tulungagung. b) Produce an acceptance model of information systems and technologies developed to improve the ease of student services. c) Describe the weaknesses found in the information system acceptance model and the technology that has been produced.Path coefficient analysis aims to see the significance of the path coefficient (regression weights estimate) to prove the effect. In the two-way test (two tailed), the results of the significant influence if the significance level of 0.05 value of the critical ratio> 1.96 and with a significance level of 0.01 the value of the critical ratio> 2.58. The suitability of the direction of the path relationship with the direction of the previously hypothesized relationship is also noted, if the direction of the relationship (positive or negative) in accordance with the critical ratio value also meets the requirements, it can be said that the influence of the tested variable has strong support. So it is possible with the existence of educational facilities it will be able to improve learning technology. Keywords: technology aceptance model, digital library